2020
DOI: 10.37899/journallaedusci.v1i6.235
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management and Higher Education: Are they Closely Related?

Abstract: An empirical study was conducted to determine the relationship between higher education and environmental management. Through the multi-stage sampling procedure, the representative sample of 180 respondents were selected for the study. Primary data were obtained with the aid of questionnaire. Data were subjected to univariate probit regression analysis. Results revealed a positive relationship between environmental management and higher education. Findings showed that tertiary education was significant at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Result support fact that farmers with access to environmental information have a higher probability to adopt knowledge, skills and processes that would lead to transformed behaviour in support of an ecologically sustainable environment. Earlier empirical studies by Haklay, (1999); Schwarte et al, (2008) and Thompson et al, (2020) confirmed that environmental decision making and technology adoption could be enhanced if the communities are given information on environmental management and climate change.…”
Section: Figure 2 Age Of Farmersmentioning
confidence: 93%
“…Result support fact that farmers with access to environmental information have a higher probability to adopt knowledge, skills and processes that would lead to transformed behaviour in support of an ecologically sustainable environment. Earlier empirical studies by Haklay, (1999); Schwarte et al, (2008) and Thompson et al, (2020) confirmed that environmental decision making and technology adoption could be enhanced if the communities are given information on environmental management and climate change.…”
Section: Figure 2 Age Of Farmersmentioning
confidence: 93%
“…Through effective character education management,especially with communication management, there will be synergistic cooperation between the government, school administrators, school committees, the community and parents of students (Wibowo, 2017). The management of character education in schools is internalized through management functions, namely planning, organizing, implementing and supervising (Thompson et al, 2020). That is, how character education is planned, how is it organized, how is it implemented and how is it supervised.…”
Section: Introductionmentioning
confidence: 99%